Stereoselective synthesis of tetrasubstituted alkenes via a sequential carbocupration and a new sulfur–lithium exchange - Unsinn, Andreas; Dunst, Cora; Knochel, Paul (Beilstein Journal of Organic Chemistry, 2012)
We have designed a new sequential carbocupration and sulfur–lithium exchange that leads stereo- and regioselectively to trisubstituted alkenyllithiums. Subsequent trapping with various electrophiles yields tetrasubstituted olefins with good control of the double-bond geometry (E/Z ratio up to 99:1). The novel sulfur–lithium exchange could be extended to the stereoselective preparation of Z-styryl lithium derivatives with almost complete retention of the double-bond geometry.
Keywords: alkenes; carbometalation; copper; regioselectivity; stereoselectivity

(untitled) - Itami, K.; Kamei, T.; Yoshida, J. (J. Am. Chem. Soc., 2003)

(untitled) - Das, J. P.; Chechik, H.; Marek, I. (Nat. Chem., 2009)

(untitled) - Zhou, C.; Larock, R. C. (Org. Lett., 2005)

(untitled) - Alonso, F.; Beletskaya, I. P.; Yus, M. (Chem. Rev., 2004)

(untitled) - Shirakawa, E.; Ikeda, D.; Masui, S.; Yoshida, M.; Hayashi, T. (J. Am. Chem. Soc., 2012)

(untitled) - Dutta, B.; Gilboa, N.; Marek, I. (J. Am. Chem. Soc., 2010)

(untitled) - Flynn, A. B.; Ogilvie, W. W. (Chem. Rev., 2007)

(untitled) - Basheer, A.; Marek, I. (Beilstein J. Org. Chem., 2010)

(untitled) - Achyutha Rao, S.; Knochel, P. (J. Am. Chem. Soc., 1991)

(untitled) - Normant, J. F.; Bourgain, M. (Tetrahedron Lett., 1971)

(untitled) - Normant, J. F.; Alexakis, A. (Synthesis, 1981)

Modern Organic Chemistry - Knochel, P. (Carbometallation of Alkenes and Alkynes. In Comprehensive Organic Syntheses: Selectivity, Strategy and Efficiency, 1992)

Functionalization of Arenes and Heteroarenes by Metalation with TMP-Bases or Metal Insertion and Synthesis of Tetrasubstituted Alkenyl Sulfides via a Cu(I)-Mediated Carbometalation - Dunst, C. (Ludwig-Maximilians-Universität München, 2011)

(untitled) - Knochel, P.; Yeh, M. C. P.; Berk, S. C.; Talbert, J. (J. Org. Chem., 1988)

(untitled) - Metzger, A.; Melzig, L.; Despotopoulou, C.; Knochel, P. (Org. Lett., 2009)

(untitled) - Melzig, L.; Metzger, A.; Knochel, P. (J. Org. Chem., 2010)

(untitled) - Satoh, T.; Takano, K.; Someya, H.; Matsuda, K. (Tetrahedron Lett., 1995)

(untitled) - Satoh, T.; Takano, K.; Ota, H.; Someya, H.; Matsuda, K.; Koyama, M. (Tetrahedron, 1998)

(untitled) - Satoh, T. (Chem. Soc. Rev., 2007)

(untitled) - Rauhut, C. B.; Melzig, L.; Knochel, P. (Org. Lett., 2008)

(untitled) - Melzig, L.; Rauhut, C. B.; Knochel, P. (Chem. Commun., 2009)

(untitled) - Stoll, A. H.; Krasovskiy, A.; Knochel, P. (Angew. Chem., 2006)
Angew. Chem. Int. Ed. 2006, 45, 606. doi:10.1002/anie.200501882

(untitled) - Korn, T. J.; Knochel, P. (Synlett, 2005)

(untitled) - Negishi, E.; King, A. O.; Okukado, N. (J. Org. Chem., 1977)

(untitled) - Negishi, E.; Okukado, N.; King, A. O.; Van Horn, D. E.; Spiegel, B. I. (J. Am. Chem. Soc., 1978)

(untitled) - Negishi, E.; Takahashi, T.; Baba, S.; Van Horn, D. E.; Okukado, N. (J. Am. Chem. Soc., 1987)

(untitled) - Negishi, E. (Acc. Chem. Res., 1982)

(untitled) - Negishi, E. (Angew. Chem., 2011)
Angew. Chem., Int. Ed. 2011, 50, 6738. doi:10.1002/anie.201101380

(untitled) - Krasovskiy, A.; Knochel, P. (Angew. Chem., 2004)
Angew. Chem., Int. Ed. 2004, 43, 3333. doi:10.1002/anie.200454084

(untitled) - Sämann, C.; Haag, B.; Knochel, P. (Chem.–Eur. J., 2012)

(untitled) - Rauhut, C. B.; Knochel, P.; Vu, V. A.; Fleming, F. F. (Org. Lett., 2008)

(untitled) - Shi, L.; Chu, Y.; Knochel, P.; Mayr, H. (Angew. Chem., 2008)
Angew. Chem. Int. Ed. 2008, 47, 202; doi:10.1002/anie.200704100

(untitled) - Kopp, F.; Knochel, P. (Org. Lett., 2007)

(untitled) - Kopp, F.; Wunderlich, S.; Knochel, P. (Chem. Commun., 2007)

(untitled) - Ila, H.; Baron, O.; Wagner, A. J.; Knochel, P. (Chem. Lett., 2006)

(untitled) - Dunst, C.; Metzger, A.; Zaburdaeva, E. A.; Knochel, P. (Synthesis, 2011)

(untitled) - Villieras, J.; Rambaud, M. (Synthesis, 1982)

(untitled) - Masure, D.; Coutrot, P.; Normant, J. F. (J. Organomet. Chem., 1982)

(untitled) - Alexakis, A.; Cahiez, G.; Normant, J. F. (Tetrahedron, 1980)

(untitled) - Normant, J. F.; Quirion, J. C.; Alexakis, A.; Masuda, Y. (Tetrahedron Lett., 1989)

(untitled) - Kienle, M.; Unsinn, A.; Knochel, P. (Angew. Chem., 2010)
Angew. Chem. Int. Ed. 2010, 49, 4751. doi:10.1002/anie.201001025

(untitled) - Truce, W. E.; Simms, J. A. (J. Am. Chem. Soc., 1956)